Characterization of a Two-way Coupling Approach for the Simulation of Fluid Flows under Cryogenic Conditions - Meireles, Rúben D. S. O. (2021)
Ice formation at lifting surfaces and engine intakes is a significant issue affecting regular aircraft operation. The icing on a wing’s leading edge perturbs the airflow around the wing, contributing to a decrease in lift and increasing drag. A step towards the understanding of droplet dynamics under cryogenics is made in the present work. An in-house developed tool is used to study the impact of droplet diameter and air humidity ratio in free-falling water droplets’ flow dynamics. The 3D Navier-Stokes equations are solved in a RANS-based two-way coupling model, which considers that the carrier fluid properties are modified by the presence of a dispersed phase, accounting for mass exchange momentum and energy between them. A Lagrangian/Eulerian formulation is employed to model each of the considered phases. The results obtained are compared with a one-way modeling approach and experimental data to infer the interacting phases’ effect in the overall process dynamics. In this way, it is possible to conclude that for high humidity content, this interaction is predominant and, consequently, needs to be taken into consideration. However, for low humidity ratios, the one-way coupling is a sufficient approximation to the experimental data.